The nosology of catatonia and DSM-5. (November 2015) - Turner, Traci; Rayfield, Amber; Pinson, Vonny; Thomas, Christopher; Carroll, Brendan T
Catatonia has been identified for over 100 years as a valid clinical entity. In its various forms and classifications, it has languished as a specifier, a subtype or as a disregarded entity. However, with the advent of DSM-5 and ICD-10, catatonia has a home of its own. This article is designed to provide the relevant psychopathology, syndrome definition and assessment tools including rating scales as they pertain to DSM-5.